Hubungan Frekuensi Pertemuan dan Kepuasan Peserta Terhadap Peningkatan Kolaborasi Pada Pelaku Usaha di Komunitas The Entrepreneurs Society - Siti Nurjanah; Natal Indra (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This research aims to find out how big a relationship the frequency of meetings and participant satisfaction has on increasing collaboration among business actors in The Entrepreneurs Society community. The research method used is a quantitative method approach with data collection techniques using probability sampling with a population of 200 community members and samples taken using the Slovin formula, namely 52 respondents. Data were collected using a questionnaire on a Likert scale. Data processing uses SPSS 29 software for instrument testing, correlation analysis and hypothesis testing. The results of the research show that both partial and simultaneous meanings of the words have the same relationship and have a positive effect between the frequency of meetings and participant satisfaction on increasing collaboration among business actors in the Entrepreneurs society community.